Možnosti vzgojitelja pri spodbujanju razvoja otrokovega interesa za branje - Erženičnik-Pačnik, Marjana (Otrok in knjiga, 2008)
The article discusses the measures and activities used by teachers to stimulate child's oral skills. We analyzed teachers' preparations for educational work in groups of fiveyear olds; on the basis of the ascertained deficiencies in the planned activities, aimed at stimulating child's oral skills, an experimental programme was made to complement teacher's work in the pre-school classes. After the experimental program has been in course for six months, its direct effects on development of child's oral abilities - demonstrated with the use of picture materials - were assessed. After the third year of child's schooling, indirect effects of this experimental program upon child's quality of and interest in reading, as well as up on his successfulness in the Slovene language, were verified. The article brings results of indirect (long-term) effects.
Keywords: predšolska vzgoja; predšolski otroci; branje; bralne zmožnosti; govorni razvoj